Peranan Rumah Baca dalam Meningkatkan Budaya Literasi pada Anak Usia Sekolah Dasar di Kota Genteng - Rika Istiqomatul Jannah; Andi Khaerun Nisa (Literatify: Trends in Library Developments, 2023)
The reading house is a place that provides non-formal education services with various sources of information as a form of concern for literacy for users. Therefore, reading houses have an important role in inculcating early on reading and writing activities. The research method used is a qualitative approach that is carried out objectively in the field. The types of data sources used in this study are primary and secondary data sources. The results of the study indicate that there is high motivation and facilities provided by the Asa Reading House in increasing early literacy. This is evidenced by the existence of various activities carried out in terms of providing learning based on learning while playing. However, children's exemplary behavior, such as interest in participating in literacy activities, is still lacking. So this has an impact on low literacy in children, especially in reading and writing activities. Literacy culture can grow well if children get motivational encouragement, both internal and external motivation.